4.23-7.2x=3.6x-9

Simple and best practice solution for 4.23-7.2x=3.6x-9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4.23-7.2x=3.6x-9 equation:


Simplifying
4.23 + -7.2x = 3.6x + -9

Reorder the terms:
4.23 + -7.2x = -9 + 3.6x

Solving
4.23 + -7.2x = -9 + 3.6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3.6x' to each side of the equation.
4.23 + -7.2x + -3.6x = -9 + 3.6x + -3.6x

Combine like terms: -7.2x + -3.6x = -10.8x
4.23 + -10.8x = -9 + 3.6x + -3.6x

Combine like terms: 3.6x + -3.6x = 0.0
4.23 + -10.8x = -9 + 0.0
4.23 + -10.8x = -9

Add '-4.23' to each side of the equation.
4.23 + -4.23 + -10.8x = -9 + -4.23

Combine like terms: 4.23 + -4.23 = 0.00
0.00 + -10.8x = -9 + -4.23
-10.8x = -9 + -4.23

Combine like terms: -9 + -4.23 = -13.23
-10.8x = -13.23

Divide each side by '-10.8'.
x = 1.225

Simplifying
x = 1.225

See similar equations:

| -2(3x+5)+4x=4 | | -12+4x=7x+17 | | -100(m-80)=4 | | (2x-5)+(4x+6)= | | 9x+44=9x-44 | | 6*-4+24= | | 6x+12y=288 | | 4=5x+3-5x | | -12790+185t=0 | | 82=2x-6 | | 4=5x+3+5x | | 2.5-8(1-5a)=-20.5 | | 4-6y=13 | | 3y-3x=-6 | | -8(3f+9)=18-5f | | -6s-5-2.5s=18.5 | | 8y+17=137 | | X-4.2=8.02 | | 27.5=-4+3(b+6.5) | | X+2.09=5 | | 0.7x=4.9 | | 7x+34=180 | | -n/18=-3 | | 2lm(x-3)=1 | | 10000=2n*(10) | | 2(x+4)+6=-22 | | 7t+4=81 | | 23.5=-5.5(8.5r-9.5) | | (6x-7)+(3x-29)=180 | | 7A-A=870 | | 5(3-2x)=5(10-3x) | | (6r+7)+(13+7r)= |

Equations solver categories